Primate Version of Modified Rankin Scale for Classifying Dysfunction in Rhesus Monkeys. Issue 5 (May 2020) - Wu, Di; Wu, Longfei; Chen, Jian; Huber, Mitchell; He, Xiaoduo; Li, Shengli; Ding, Yuchuan; Ji, Xunming
Abstract : Background and Purpose—: Nonhuman primates are increasingly used in translational studies of ischemic stroke. However, current scoring systems in monkeys (eg, Nonhuman Primate Stroke Scale) do not focus on impairments in activities of daily living, so clinically relevant data are scarce for evaluating functional deficits in this model. Methods—: Here, we referenced the modified Rankin Scale to provide a primate version of Rankin Scale (pRS) for ranking neurological dysfunction in monkeys following stroke. We selected hand function and strength, level of activity, and general mobility as the main components of pRS. We also analyzed interobserver variability. Results—: pRS is a simple scale with only 6 levels. Functional deficit can be easily classified into none (category 0), slight (categories 1–2), moderate (category 3–4), and severe disabilities (category 5) based on pRS. We validated this scoring system on 11 monkeys, all with varying levels of neurological dysfunction following stroke, assessed by blinded testers. After a short training period, both technicians and neurology residents were able to achieve a high level of consistency using this scoring system. Conclusions—: pRS is a simple and reliable functional scale, similar to the widely used modified Rankin Scale, for evaluating long-term neurological dysfunction in nonhuman primates. We recommend further validation studies and analyses. Abstract : Supplemental Digital Content is available in the text.